Bisphosphonates: Current applications in Osteoporosis and Cancer Therapy - Poma Carmona, Augusto (1999)
Bisphosphonates are antiresorptive agents with high affinity for hidroxiapatite crystals. They are not degraded by pyrophosphatases. Their main indications are treatment of post-menopausic osteoporosis, corticosteroid-induced osteoporosis, Paget´s disease, neoplasm-induced hypercalcemia and osteolytic bone disease by cancer.